SUPPORTING LANGUAGE DEVELOPMENT IN MIXED-ABILITY CLASSROOMS - Rashidova Laziza Ilhomovna (TADQIQOTLAR, 2026)
Abstract Supporting language development in mixed-ability classrooms is a critical challenge in contemporary English language teaching, where students differ widely in proficiency, learning styles, prior knowledge, and motivation. This article explores strategies to enhance language acquisition in heterogeneous settings by employing differentiated instruction, scaffolding, collaborative learning, formative assessment, and technology integration. Emphasis is placed on adapting content, process, product, and learning environment to student readiness, interests, and learning profiles. Practical approaches for vocabulary, grammar, reading, writing, speaking, and listening development are discussed, alongside methods to promote learner autonomy, engagement, and inclusive participation. The article highlights the importance of culturally responsive materials, ongoing professional development, and reflective teaching practices for sustaining effective language support. Ultimately, implementing these strategies fosters communicative competence, confidence, critical thinking, and lifelong learning skills among all learners in mixed-ability classrooms.